2021
DOI: 10.3390/ijerph182413406
|View full text |Cite
|
Sign up to set email alerts
|

Personal Safety and Fear of Sexual Harassment among Female Garment Workers in Bangladesh

Abstract: Personal safety and fear of sexual harassment may discourage women from participating at work and in public life, limiting their life opportunities. The study proposed to determine personal safety and fear of sexual harassment among female garment workers in Bangladesh. This cross-sectional study was conducted among 201 female garment workers from Dhaka and Chittagong cities. Participants were selected using snowballing sampling techniques with the data collected by using anonymised questionnaires. The Pearson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Our results are consistent with a prior study that showed that anti-sexual harassment programs can be effective for improving knowledge and attitudes among nurse aides in long term care facilities [24]. That study noted that fear of speaking up and not knowing how to respond were associated with less personal safety [19], [24], [25]. Another study found a significant positive correlation between personal safety and the fear of sexual harassment and demonstrated that a culturally sensitive and institutionally-based approach was not only useful at the individual level, it positively affected workplace culture for women at the institutional level [26].…”
Section: Effectiveness Of the Sexual Harassment Prevention Programsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with a prior study that showed that anti-sexual harassment programs can be effective for improving knowledge and attitudes among nurse aides in long term care facilities [24]. That study noted that fear of speaking up and not knowing how to respond were associated with less personal safety [19], [24], [25]. Another study found a significant positive correlation between personal safety and the fear of sexual harassment and demonstrated that a culturally sensitive and institutionally-based approach was not only useful at the individual level, it positively affected workplace culture for women at the institutional level [26].…”
Section: Effectiveness Of the Sexual Harassment Prevention Programsupporting
confidence: 92%
“…The results were statistically significant p=0.001, so the primary hypothesis was confirmed that participating in the sexual harassment program is associated with more knowledge about sexual harassment and ways of dealing with it. Our results are consistent with a prior study that showed that anti-sexual harassment programs can be effective for improving knowledge and attitudes among nurse aides in long term care facilities [24]. That study noted that fear of speaking up and not knowing how to respond were associated with less personal safety [19], [24], [25].…”
Section: Effectiveness Of the Sexual Harassment Prevention Programsupporting
confidence: 92%
See 2 more Smart Citations